Mems/Nems (1) Handbook Techniques and Applications Design Methods, (2) Fabrication Techniques, (3) Manufacturing Methods, (4) Sensors and Actuators, (5) Medical Applications and MOEMS - Leondes, Cornelius T. (Springer US : Imprint: Springer, 2006)
Micro-Electro Mechanical Systems (MEMS) is the integration of mechanical elements, sensors, actuators, and electronics on a common silicon substrate. While the electronics are fabricated using integrated circuit (IC) process sequences (e.g., CMOS, Bipolar, or BICMOS processes), the micromechanical components are fabricated using compatible micromachining processes that selectively etch away parts of the silicon wafer or add new structural layers to form the mechanical and electromechanical devices. MEMS promises to revolutionize nearly every product category by bringing together silicon-based microelectronics with micromachining technology, thereby, making possible the realization of complete systems-on-a-chip. Microelectromechanic systems will revolutionize the design of electronics products and enable the creation of entirely new product categories. Through miniaturization, batch fabrication, and integration with electronics, this technology will enable the development of smart products by providing the required interface between the available computational power and physical world through the perception and control capabilities of micro devices or systems (e.g., microsensors and microactuators). Micromechanical devices and systems are inherently smaller, lighter and faster than their macroscopic counterparts, and in many cases are also more precise. MEMS devices are emerging as a product differentiators in numerous markets. MEMS technology is expected to have enormous opportunities in the commercial markets due to the low-cost, high functionality, and small size and weight of the devices. MEMS technology allows much more functionality to be placed within a given space than conventional technologies. A special class of MEMS is optical MEMS technology, also referred to as MOEMS (Micro Optical Mechanical Systems). MOEMS have become increasingly important in the development of many networks, telecommunications and optical systems. Potential MOEMS applications include optical data storage, optical sensors, bead mounted displays and projection systems. State-of-the-art devices include torsional mirrors, digital micromirror devices, laser scanners, optical shutters, microooptical switches, and micromachined corner cube reflectors. Nanoelectromechanical systems (NEMS) are MEMS scaled to submicrometer dimensions, to exploit the mechanical degree of freedom on the nanometer scale. In this size regime, it is possible to attain extremely high fundamental frequencies while simultaneously preserving high mechanical responsivity. This combination of attributes translates directly into high force sensitivity, operability at ultra-low power, and the ability to induce non-linearity with very modest control forces, leading to potential payoffs in a diverse range of fields from medicine to biotechnology. The MEMS/NEMS HANDBOOK consists of five volumes and will provide a significant and uniquely comprehensive reference source for research workers, practitioners, computer scientists, students, technologists and others on the international scene for years to come: (1) MEMS/NEMS Design Methods in MEMS/NEMS (2) Fabrication Techniques in MEMS/NEMS (3) Manufacturing Methods (4) Sensors & Actuators (5) Medical Applications and MOEMS This landmark work features contributions from more than 100 of the world's foremost authorities on the key technologies and the greatly significant application areas of MEMS/NEMS. The contributors come from industry, government and academia.